THE EFFECTIVENESS OF THE EDUCATIONAL-DIAGNOSIS MEETING TYPE OF DISCUSSION METHOD TO IMPROVE CULTURAL ARTS LEARNING OUTCOMES IN CLASS VIII-5 AT SMP NEGERI 1 PADANGSIDIMPUAN - NUR LENA (JURNAL LINER (Language Intelligence and Educational Research), 2022)
This research is a class action research and conducted online in two research cycles in Class VIII-5 at SMP Negeri 1 Padangsidimpuan. The number of participants involved were 25 students, plus the researcher who acted as participant observer. For data validation, researchers recorded activities directly during the learning process. This study aims to find out how the Discussion learning model in the form of The Educational-Diagnosis Meeting is able to improve student learning outcomes in participating in Cultural Arts learning activities in Class VIII-5 at SMP Negeri 1 Padangsidimpuan. Data were collected through observation and document review and analysis of learning video recordings. The findings were then analyzed qualitatively based on the theories put forward in the study. This research proves the following points. The implementation of the Educational-diagnosis meeting type of discussion learning model was able to improve the learning outcomes of Cultural Arts in Class VIII-5 at SMP Negeri 1 Padangsidimpuan. Discussing folk songs is able to develop students' speaking and critical thinking skills. The implementation of online classes expects the maximum effort of the teacher in motivating students to take part in learning activities. Technical constraints still often cause interference in online learning activities. In holding the Educational-Diagnosis Meeting Discussion learning activities, teachers should have extensive knowledge of the issues discussed, so that when students ask questions, the teacher can provide satisfactory answers. Further research on the issues above is still needed to obtain more satisfactory results. Keywords: Learning Outcomes, Cultural Arts, Discussion of The Educational-Diagnosis Meeting, Qualitative, Class Action Research through online, Junior High School